First isolation of the Sindbis virus in mosquitoes from southwestern Spain reveals a new recent introduction from Africa - Rafael Gutiérrez-López; María José Ruiz-López; Juan Ledesma; Sergio Magallanes; Cristina Nieto; Santiago Ruiz; Carolina Sanchez-Peña; Ulises Ameyugo; Juan Camacho; Sarai Varona; Isabel Cuesta; Isabel Jado-García; et al. (One Health)
Sindbis virus (SINV), is an Alphavirus of the family Togaviridae. This zoonotic arbovirus is transmitted by mosquitoes, primarily from the Culex genus, with bird species acting as amplifying vertebrate hosts. Occasionally it can also affect humans that are accidental hosts. SINV genotype I (SINV-I) has been isolated in mosquitoes and birds in South Africa and Northern Europe, producing fever outbreaks. In the last decades, there were several detections of SINV in Europe. In 2022, during the West Nile virus (WNV) mosquito surveillance program in Andalucía (Spain) implemented by the regional health administration, we detected the presence of both SINV and WNV in a Culex perexiguus pool, representing the first detection of SINV in Spain. After this finding, we screened 1149 mosquito pools to determine the status of SINV circulation in western Andalucía. We identified for the first time the presence of SINV in five different mosquito species. Culex perexiguus presented the highest infection rate by SINV. In addition, SINV was geographically widespread and distributed in four out of the five Andalucía's provinces studied, with Cadiz presenting the highest infection rate. All SINV genomes from Southwestern Spain characterised in this study belonged to SINV-I, previously detected in Europe and Africa. These isolated SINV-I strains presented low molecular variation among them and in the phylogenomic analyses they formed a monophyletic group that clustered with strains from Algeria and Kenya. These results suggest that, around 2017, a single new SINV introduction into the European continent occurred, probably from Northern (Algeria) or Central Africa.